ANALISIS SEMIOTIKA PADA TRILOGI ALINA DALAM ANTOLOGI CERPEN SEPOTONG SENJA UNTUK PACARKU KARYA SENO GUMIRA ADJI DARMA - Sudrajat, Rochmat Tri; Muhamad, Fadel (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2020)
This article discusses a surrealist short story. The approach used in this study is Pierce's semiotics approach, which is to discuss the signs in the short story anthology entitled "A Piece of Dusk for My Girl" by Seno Gumira Adji Darma. These signs have a certain meaning / significance closely related to the community system. The sign can be seen from the use of the language used. The signs that exist in literary works must be revealed to find out the message to be conveyed by the author. This study aims to determine the relationship between the sign with the reference based on the nature of the ground, (1) Sinsign, (2) Qualisign, and (3) Legisign. With semiotics, readers can capture the message or intent of a short story that is not clearly displayed by the author. The research method used is descriptive qualitative. This article examines the trilogy that exists in the short story anthology entitled A Twilight Piece for My Boyfriend, Answer Alina, Postman in a total of 41 pages. In the shorts story trilogy, researches found 21 interrelated signs. The sign is examined with Pierce’s semiotics it becomes a series of meaningful stories so that the message can be clearly known.